Virological and clinical cure in COVID‐19 patients treated with hydroxychloroquine: A systematic review and meta‐analysis. Issue 7 (3rd May 2020) - Sarma, Phulen; Kaur, Hardeep; Kumar, Harish; Mahendru, Dhruv; Avti, Pramod; Bhattacharyya, Anusuya; Prajapat, Manisha; Shekhar, Nishant; Kumar, Subodh; Singh, Rahul; Singh, Ashutosh; Dhibar, Deba Prasad; et al.
Abstract: Following the demonstration of the efficacy of hydroxychloroquine against severe acute respiratory syndrome coronavirus 2 in vitro, many trials started to evaluate its efficacy in clinical settings. However, no systematic review and meta‐analysis have addressed the issue of the safety and efficacy of hydroxychloroquine (HCQ) in coronavirus disease 2019. We conducted a systematic review and meta‐analysis with the objectives of evaluation of safety and efficacy of HCQ alone or in combination in terms of "time to clinical cure, " "virological cure, " "death or clinical worsening of disease, " "radiological progression, " and safety. RevMan was used for meta‐analysis. We searched 16 literature databases out of which seven studies (n = 1358) were included in the systematic review. In terms of clinical cure, two studies reported possible benefit in "time to body temperature normalization" and one study reported less "cough days" in the HCQ arm. Treatment with HCQ resulted in less number of cases showing the radiological progression of lung disease (odds ratio [OR], 0.31, 95% confidence interval [CI], 0.11‐0.9). No difference was observed in virological cure (OR, 2.37, 95% CI, 0.13‐44.53), death or clinical worsening of disease (OR, 1.37, 95% CI, 1.37‐21.97), and safety (OR, 2.19, 95% CI, 0.59‐8.18), when compared with the control/conventional treatment. Five studies reported either the safety or efficacy of HCQ + azithromycin. Although seems safe and effective, more data are required for a definitive conclusion. HCQ seems to be promising in terms of less number of cases with radiological progression with a comparable safety profile to control/conventional treatment. We need more data to come to a definite conclusion. Research Highlights: Following the demonstration of the efficacy of hydroxychloroquine (HCQ) against severe acute respiratory syndrome coronavirus 2 in vitro, many trials were started to evaluate its efficacy in clinical settings. However, no systematic review and meta‐analysis have addressed the issue to the safety and efficacy of HCQ in coronavirus disease 2019 (COVID‐19). We searched 16 literature databases finally seven articles were identified, which evaluated the therapeutic efficacy of HCQ either alone or in combination with azithromycin in COVID‐19. RevMan was used for meta‐analysis. For continuous outcome, mean difference and for a dichotomous outcome, odds ratio with 95% confidence interval was calculated. Model selection (fixed effect or random effect) was done on the basis of heterogeneity among different studies. Three studies reported the safety and efficacy of HCQ vs control/conventional treatment in terms of safety and efficacy in COVID‐19. Treatment with HCQ resulted in benefit in terms of less number of cases with radiological progression with no increase in adverse events when compared with control/conventional/standard treatment. We can also expect a benefit in terms of a number of days to body temperature normalization and number of cough days. However, at this current point of time, no difference was seen in terms of virological cure on day 6 to 7 postinitiation of therapy and composite death or worsening of the disease. Four studies reported efficacy and five studies reported safety of the HCQ + azithromycin combination (out of which three studies from the same group). Although the combination of HCQ + azithromycin seems to be effective and safe, we need more controlled studies to come to an effective conclusion. However, electrocardiographic monitoring is essential while using this combination due to the risk of QT prolongation.